Local Positioning for Wireless Sensor Networks - Ellinger, Frank; Eickhoff, Ralf; Gierlich, Roland; Hüttner, Jörg; Ziroff, Andreas; Wehrli, Silvan; Ußmüller, Thomas; Carls, Jörg; Subramanian, Viswanathan; Krcmar, Marko; Mosshammer, Ralf; Spiegel, Solon; et al. (Globecom Workshops, 2007 IEEE, 2007)
This workshop paper gives an overview of local positioning and tracking principles for wireless sensor networks including recent results of the European project RESOLUTION (reconfigurable systems for mobile local communication and positioning). Measurements of a first demonstrator applying a frequency modulated continuous wave (FMCW) radar principle are presented. The unlicensed ISM band around 5.8 GHz, 150 MHz bandwidth and less than 25 mW effective isotropic radiated transmit power are used. Excellent 3-D positioning accuracies in the order of 4 cm in an anechoic chamber and 18 cm in a conference hall with strong multipath and area of 800 m2 are measured. Furthermore, the results of optimized radio frequency integrated circuits and a suitable compact flash card are outlined.
elib2cris::1512001600,ellinger2007a
Keywords: BiCMOS; FMCW; integrated circuits; local positioning; radar; radio frequencies; tracking; wireless sensors; Anechoic chambers; Area measurement; Bandwidth; Frequency measurement; Frequency modulation; Mobile communication; Position measurement